Vegetable Consumption by Older Adults in Japan - Lee, Andy; Hirayama, Fumi (Nova Science Publishers, Inc., 2012)
Background: The importance and health benefits of vegetables are well known, while the nutritional requirements of older adults are different from those of younger adults. Objective: This study investigated vegetable consumption by gender and age groups among Japanese older adults. Method: A total of 558 eligible participants (341 men and 217 women) aged 55 to 75 years were recruited from 10 districts/prefectures in middle and southern Japan. Information on habitual vegetable consumption was obtained by face-to-face interviews using a validated and reliable food frequency questionnaire. Results: Women were found to consume more vegetables (mean 274, SD 166 g/day) than men (mean 207, SD 135 g/day) overall (p < 0.001) and across age groups 55-59, 60-64, 65-69 and 70-75 years. However, the intake levels of both genders did not vary significantly between age groups. The Japanese government has recommended an intake level of 350g or more per day for individuals. It is alarming that 83% of participants did not eat an adequate amount of vegetables. Conclusion: Japanese older adults especially men should be encouraged to increase their vegetable consumption in order to maintain their health and well-being.